Effects of Dietary Macleaya cordata Extract Containing Isoquinoline Alkaloids Supplementation as an Alternative to Antibiotics in the Diets on Growth Performance and Liver Health of Broiler Chickens - Liu, Yang; Li, Yang; Niu, Jiaxing; Liu, Hua; Jiao, Ning; Huang, Libo; Jiang, Shuzhen; Yan, Lei; Yang, Weiren (Frontiers in Veterinary Science, 2022)
This study aimed to investigate the effects of dietary supplementation with Macleaya Cordata extract (MCE) containing protopine and allotypotopine on growth performance and liver health in broiler chickens. A total of 486 1-day-old male AA broiler chickens were randomly assigned to the following three groups: 1) control (CON) group, broiler chickens fed a basal diet; 2) AGP group (positive control), broiler chickens fed a basal diet supplemented with 50 mg/kg aureomycin; 3) MCE group, broiler chickens fed a basal diet supplemented with 0.6 mg/kg MCE including 0.4 mg/kg protopine and 0.2 mg/kg allotypotopine. The results showed that MCE group had significantly higher final body weight and average daily gain from d 0 to 42 than the other groups (P < 0.05), and groups MCE and AGP both had significantly lower feed-to-gain ratio from d 0 to 42 than CON group (P < 0.05). Serum total protein, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, total cholesterol, glucose, immunoglobulin A, immunoglobulin M and complements (C3, C4) concentrations in MCE group were significantly higher than in CON group (P < 0.05). Dietary MCE or aureomycin supplementation significantly reduced hepatic contents of 8-hydroxy-2’-deoxyguanosine, malondialdehyde, interleukin (IL)-1β, IL-6, NLRs family pyrin domain containing 3 (NLRP3) and caspase-1 in the liver (P < 0.05). Moreover, MCE or aureomycin supplementation significantly inhibited mRNA expressions of Toll-like receptor 4, myeloid differentiation factor 88, nuclear factor-κB, and NLRP3, as well as the expression ratio of Bax to Bcl-2 mRNA (P < 0.05). Therefore, our study suggested that dietary supplementation with 0.6 mg/kg MCE containing protopine and allocryptopine improved growth performance and benefited to liver health in broiler chickens possibly through inhibiting caspase-1-induced pyroptosis by inactivating TLR4/MyD88/NF-κB/NLRP3 signaling pathway, and provided support for the application of MCE containing protopine and allocryptopine as an alternative to antibiotics in feed industry.